Influence of the radial stem composition on the thermal behaviour of miscanthus and sorghum genotypes. (1st July 2017) - Chupin, Lucie; Ridder, Dieter de; Clément-Vidal, Anne; Soutiras, Armelle; Gineau, Emilie; Mouille, Grégory; Arnoult, Stéphanie; Brancourt-Hulmel, Maryse; Lapierre, Catherine; Pot, David; Vincent, Luc; Mija, Alice; et al.
Highlights: Thermal resistance of plants is not simply related to their composition. Thermal analysis is only sensitive to very large variations of compositions. Interplay between components is blurring the thermal response. Abstract: The hypothesis made is that thermal resistance of sorghum and miscanthus stem pieces taken at well-defined positions of the stem is simply related to their biochemical composition. For miscanthus, two different genotypes and two internode levels were selected. For each region, the stem was divided into three radial layers. For sorghum, two different genotypes were selected and the stem was divided into the same three radial layers. The results show that the thermal analysis is only sensitive to very large variations of compositions. But aside of such large composition differences, it is impossible to correlate thermal effects to biochemical composition even on very small size, well-identified pieces of plant materials. The interplay between sugar-based components, lignin and minerals is totally blurring the thermal response. Extreme care must be exercised when willing to explain why a given plant material has a thermal behaviour different of another plant material.